Survey Analysis Of Real Demand Of The Non Customer Community In Perumda Tirtauli Pematangsiantar City - Pinondang Nainggolan; Anggiat Sinurat; Marulam MT Simarmata; Wico Jontarudi Tarigan (Program Studi Ekonomi Pembangunan Fakultas Ekononomi Universitas Simalungun, 2024)
This research aims to find out the real demand survey of the non-customer community of Perumda Tirta Uli, Pematang Siantar City, as well as to find out the reasons why they are not willing to register as customers of the company. The research design is a descriptive method with an in-depth survey. Data collection techniques through questionnaires, interviews and documentaries. Data analysis techniques with stages of data tabulation, data compilation, data analysis of demand factors, supply, socio-economics, customer willingness to pay for water and customer ability to pay water bills. The research results concluded: (1) the reason people were not willing to register as customers was because from the start they had used drilled wells (35%), because installation costs were high (19%), and distribution pipes were far away (6%). while the percentage of reasons for the water not being clear is low (6%), water distribution is often jammed (16%) and the reason for not being able to pay is only (14%). non-customers who have never applied for installing a water connection pipe (92.06%), only 7.94% have applied but it was canceled. It is recommended that the use of drilled wells must be controlled by the regional government through public awareness outreach and/or the issuance of Regional Regulations, so that underground water extraction (ABT) is not excessive